Examples with solutions for Powers of a Fraction: Calculating powers with negative exponents

Exercise #1

Insert the corresponding expression:

(1013)4= \left(\frac{10}{13}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve the expression (1013)4\left(\frac{10}{13}\right)^{-4}, we start by applying the rule for dividing exponents is:

104134\frac{10^{-4}}{13^{-4}}, which maintains the negative exponent but as separate components of fraction resulting in the same value.

Consequently, the expression (1013)4\left(\frac{10}{13}\right)^{-4} equates to 104134\frac{10^{-4}}{13^{-4}}.

By comparing this with the presented choices, we identify that option (2):

104134 \frac{10^{-4}}{13^{-4}}

matches correctly with our conversion of the original expression.

Therefore, the correct expression is 104134\frac{10^{-4}}{13^{-4}}.

Answer

104134 \frac{10^{-4}}{13^{-4}}

Exercise #2

Insert the corresponding expression:

(120)7= \left(\frac{1}{20}\right)^{-7}=

Video Solution

Step-by-Step Solution

To simplify the expression (120)7 \left(\frac{1}{20}\right)^{-7} , we will apply the rule for negative exponents. The key idea is that a negative exponent indicates taking the reciprocal and converting the exponent to a positive:

  • Start with the expression: (120)7 \left(\frac{1}{20}\right)^{-7} .
  • Apply the negative exponent rule: (1a)n=an \left(\frac{1}{a}\right)^{-n} = a^n .
  • For our expression: (120)7 \left(\frac{1}{20}\right)^{-7} becomes 207 20^7 .

Therefore, (120)7 \left(\frac{1}{20}\right)^{-7} simplifies to 207 20^7 .

Thus, the correct answer is 207 20^7 .

Answer

207 20^7

Exercise #3

Insert the corresponding expression:

(160)4= \left(\frac{1}{60}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve for (160)4 \left(\frac{1}{60}\right)^{-4} , we apply the rule for negative exponents.

Step 1: Use the negative exponent rule: For any non-zero number a a , an=1an a^{-n} = \frac{1}{a^n} . Thus,

(160)4=(601)4 \left(\frac{1}{60}\right)^{-4} = \left(\frac{60}{1}\right)^4 .

Step 2: Simplify (601)4\left(\frac{60}{1}\right)^4 by recognizing the identity 601=60\frac{60}{1} = 60, so it follows that:

(601)4=604 \left(\frac{60}{1}\right)^4 = 60^4 .

Therefore, the simplified expression is 604 60^4 .

The correct answer is 604 60^4

Answer

604 60^4

Exercise #4

Insert the corresponding expression:

(1521)3= \left(\frac{15}{21}\right)^{-3}=

Video Solution

Step-by-Step Solution

To solve the expression (1521)3 \left(\frac{15}{21}\right)^{-3} , we will apply the rule for converting negative exponents into positive exponents.

Step 1: Recognize that the negative exponent indicates the reciprocal of the base raised to the positive equivalent of the exponent. Thus, we use the formula:

(ab)n=(ba)n\left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^n.

Step 2: Apply this formula to our expression:

(1521)3=(2115)3\left(\frac{15}{21}\right)^{-3} = \left(\frac{21}{15}\right)^3.

Therefore, the solution to the problem is (2115)3 \left(\frac{21}{15}\right)^3 , which corresponds to choice 3.

Answer

(2115)3 \left(\frac{21}{15}\right)^3

Exercise #5

Insert the corresponding expression:

(1013)2= \left(\frac{10}{13}\right)^{-2}=

Video Solution

Step-by-Step Solution

To solve the problem, apply the negative exponent rule:

  • For any fraction ab\frac{a}{b} with a negative exponent n-n, apply the rule: (ab)n=(ba)n\left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^{n}.

Apply this rule to the given expression (1013)2\left(\frac{10}{13}\right)^{-2}:

(1013)2=(1310)2 \left(\frac{10}{13}\right)^{-2} = \left(\frac{13}{10}\right)^{2}

Therefore, the correct expression with a positive exponent is (1310)2\left(\frac{13}{10}\right)^{2}.

In the provided choices, this is option:

  • (1310)2 \left(\frac{13}{10}\right)^2

Hence, the correct expression is (1310)2\left(\frac{13}{10}\right)^2.

Answer

(1310)2 \left(\frac{13}{10}\right)^2

Exercise #6

Insert the corresponding expression:

(25)2= \left(\frac{2}{5}\right)^{-2}=

Video Solution

Step-by-Step Solution

To solve the problem of converting (25)2\left(\frac{2}{5}\right)^{-2} to positive exponents, we use the rule for negative exponents:

Negative exponent rule states:

  • (ab)n=(ba)n\left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^n — This indicates that we invert the fraction and change the sign of the exponent to positive.

Given expression: (25)2\left(\frac{2}{5}\right)^{-2}.

Application: By using the rule, the negative exponent instructs us to reciprocate the fraction:

(25)2=(52)2\left(\frac{2}{5}\right)^{-2} = \left(\frac{5}{2}\right)^{2}.

The positive exponent (2)(2) indicates the expression is squared. Thus, our action is complete with no further action required.

Thus, the correctly transformed expression of (25)2\left(\frac{2}{5}\right)^{-2} is indeed:

(52)2 \left(\frac{5}{2}\right)^2 .

Answer

(52)2 \left(\frac{5}{2}\right)^2

Exercise #7

Insert the corresponding expression:

(1017)5= \left(\frac{10}{17}\right)^{-5}=

Video Solution

Step-by-Step Solution

To solve the problem, we will follow these steps:

  • Step 1: Identify the expression and apply the rule for negative exponents.
  • Step 2: Take the reciprocal of the given fraction 1017 \frac{10}{17} .
  • Step 3: Raise the reciprocal to the positive power of 5.

Now, let's work through each step:
Step 1: We start with the problem expression (1017)5 \left(\frac{10}{17}\right)^{-5} . According to the laws of exponents, a negative exponent means the reciprocal of the base should be raised to the positive of that exponent.
Step 2: Take the reciprocal of 1017 \frac{10}{17} , which is 1710 \frac{17}{10} .
Step 3: Raise the reciprocal 1710 \frac{17}{10} to the power of 5, resulting in (1710)5 \left(\frac{17}{10}\right)^5 .

Therefore, the equivalent expression is (1710)5 \left(\frac{17}{10}\right)^5 .

Answer

(1710)5 \left(\frac{17}{10}\right)^5

Exercise #8

Insert the corresponding expression:

(13)4= \left(\frac{1}{3}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given expression with a negative exponent.
  • Step 2: Apply the rule for negative exponents, which allows us to convert the expression into a positive exponent form.
  • Step 3: Perform the calculation of the new expression.

Now, let's work through each step:

Step 1: The expression given is (13)4 \left(\frac{1}{3}\right)^{-4} , which involves a negative exponent.

Step 2: According to the exponent rule (ab)n=(ba)n \left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^n , we can rewrite the expression with a positive exponent by inverting the fraction:

(13)4=(31)4=34 \left(\frac{1}{3}\right)^{-4} = \left(\frac{3}{1}\right)^4 = 3^4 .

Step 3: Calculate 34 3^4 .

The calculation 34 3^4 is as follows:

34=3×3×3×3=81 3^4 = 3 \times 3 \times 3 \times 3 = 81 .

However, since the problem specifically asks for the corresponding expression before calculation to numerical form, the answer remains 34 3^4 .

Therefore, the answer to the problem, in terms of an equivalent expression, is 34 3^4 .

Answer

34 3^4

Exercise #9

Insert the corresponding expression:

(38)5= \left(\frac{3}{8}\right)^{-5}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given fraction and the negative exponent.
  • Step 2: Apply the conversion rule from negative to positive exponents on fractions.

Now, let's work through each step:
Step 1: The given expression is (38)5 \left(\frac{3}{8}\right)^{-5} . This indicates a fraction raised to a negative power.
Step 2: Applying the rule (ab)n=(ba)n(\frac{a}{b})^{-n} = (\frac{b}{a})^{n}, we invert the fraction and change the exponent to positive. This gives us the expression (83)5 \left(\frac{8}{3}\right)^5 .

Therefore, the solution to the problem is (83)5 \left(\frac{8}{3}\right)^5 .

Answer

(83)5 \left(\frac{8}{3}\right)^5

Exercise #10

Insert the corresponding expression:

(56)3= \left(\frac{5}{6}\right)^{-3}=

Video Solution

Step-by-Step Solution

To solve this problem, we need to convert the expression (56)3\left(\frac{5}{6}\right)^{-3} into a form with positive exponents.

The negative exponent rule states that xn=1xnx^{-n} = \frac{1}{x^n}. Applying this to our given fraction:

(56)3=(65)3\left(\frac{5}{6}\right)^{-3} = \left(\frac{6}{5}\right)^{3}.

This means we take the reciprocal of 56\frac{5}{6}, which is 65\frac{6}{5}, and then raise it to the power of 3.

Therefore, the correct expression is (65)3\left(\frac{6}{5}\right)^3.

This matches choice 1 in the list of possible answers.

Answer

(65)3 \left(\frac{6}{5}\right)^3

Exercise #11

Insert the corresponding expression:

(7×11×193×12×15)4= \left(\frac{7\times11\times19}{3\times12\times15}\right)^{-4}=

Video Solution

Step-by-Step Solution

The given expression is:
(7×11×193×12×15)4 \left(\frac{7\times11\times19}{3\times12\times15}\right)^{-4}

To solve this expression, we need to apply the rules of exponents, specifically the rule for powers of a fraction. For any fraction(ab)n \left(\frac{a}{b}\right)^{-n} , the expression is equivalent to(ba)n \left(\frac{b}{a}\right)^n .
Therefore, negative exponents indicate that the fraction should be flipped and raised to the positive of that exponent.

Substitute the terms into this formula:
1. Flip the fraction: (3×12×157×11×19) \left(\frac{3\times12\times15}{7\times11\times19}\right)
2. Raise both numerator and denominator to the power of 4:
Thus, we have:
(3×12×157×11×19)4 \left(\frac{3\times12\times15}{7\times11\times19}\right)^{4}

Now evaluating each term individually:
- In the numerator:
- 34×124×154 3^4\times12^4\times15^4
- In the denominator:
- 74×114×194 7^4\times11^4\times19^4

Applying the negative exponent rule, each individual factor in both numerator and denominator should be inverted, altering the exponents to negative:
1. Numerator becomes: 34×124×154 3^{-4}\times12^{-4}\times15^{-4}
2. Denominator becomes: 74×114×194 7^{-4}\times11^{-4}\times19^{-4}

Rewriting the expression, we achieve:
74×114×19434×124×154 \frac{7^{-4}\times11^{-4}\times19^{-4}}{3^{-4}\times12^{-4}\times15^{-4}}

This matches precisely the provided solution.

The solution to the question is:74×114×19434×124×154 \frac{7^{-4}\times11^{-4}\times19^{-4}}{3^{-4}\times12^{-4}\times15^{-4}}

Answer

74×114×19434×124×154 \frac{7^{-4}\times11^{-4}\times19^{-4}}{3^{-4}\times12^{-4}\times15^{-4}}

Exercise #12

(23)4=? (\frac{2}{3})^{-4}=\text{?}

Video Solution

Step-by-Step Solution

We use the formula:

(ab)n=(ba)n (\frac{a}{b})^{-n}=(\frac{b}{a})^n

Therefore, we obtain:

(32)4 (\frac{3}{2})^4

We use the formula:

(ba)n=bnan (\frac{b}{a})^n=\frac{b^n}{a^n}

Therefore, we obtain:

3424=3×3×3×32×2×2×2=8116 \frac{3^4}{2^4}=\frac{3\times3\times3\times3}{2\times2\times2\times2}=\frac{81}{16}

Answer

8116 \frac{81}{16}

Exercise #13

Insert the corresponding expression:

(25)3= \left(\frac{2}{5}\right)^{-3}=

Video Solution

Answer

2353 \frac{2^{-3}}{5^{-3}}

Exercise #14

Insert the corresponding expression:

(14)2= \left(\frac{1}{4}\right)^{-2}=

Video Solution

Answer

1242 \frac{1^{-2}}{4^{-2}}

Exercise #15

Insert the corresponding expression:

(23)11= \left(\frac{2}{3}\right)^{-11}=

Video Solution

Answer

211311 \frac{2^{-11}}{3^{-11}}

Exercise #16

Insert the corresponding expression:

(49)5= \left(\frac{4}{9}\right)^{-5}=

Video Solution

Answer

4595 \frac{4^{-5}}{9^{-5}}

Exercise #17

Insert the corresponding expression:

(37)4= \left(\frac{3}{7}\right)^{-4}=

Video Solution

Answer

3474 \frac{3^{-4}}{7^{-4}}

Exercise #18

Insert the corresponding expression:

(57)7= \left(\frac{5}{7}\right)^{-7}=

Video Solution

Answer

(75)7 \left(\frac{7}{5}\right)^7

Exercise #19

Insert the corresponding expression:

(5×8×621×23×19)2= \left(\frac{5\times8\times6}{21\times23\times19}\right)^{-2}=

Video Solution

Answer

(5×8×6)2(21×23×19)2 \frac{\left(5\times8\times6\right)^{-2}}{\left(21\times23\times19\right)^{-2}}

Exercise #20

Insert the corresponding expression:

(4×85×17×3)4= \left(\frac{4\times8}{5\times17\times3}\right)^{-4}=

Video Solution

Answer

(4×8)4(5×17×3)4 \frac{\left(4\times8\right)^{-4}}{\left(5\times17\times3\right)^{-4}}